The whole town's talking eaudiobook Elmwood springs series, book 4. - Flagg, Fannie (Random House Audio, 2016)
NEW YORK TIMES BESTSELLER • The bestselling author of Fried Green Tomatoes at the Whistle Stop Cafe is at her superb best in this fun-loving, moving novel about what it means to be truly alive. WINNER OF THE SOUTHERN BOOK PRIZE  Elmwood Springs, Missouri, is a small town like any other, but something strange is happening at the cemetery. Still Meadows, as it’s called, is anything but still. Original, profound, The Whole Town’s Talking, a novel in the tradition of Thornton Wilder’s Our Town and Flagg’s own Can’t Wait to Get to Heaven, tells the story of Lordor Nordstrom, his Swedish mail-order bride, Katrina, and their neighbors and descendants as they live, love, die, and carry on in mysterious and surprising ways. Lordor Nordstrom created, in his wisdom, not only a lively town and a prosperous legacy for himself but also a beautiful final resting place for his family, friends, and neighbors yet to come. “Resting place” turns out to be a bit of a misnomer, however. Odd things begin to happen, and it starts the whole town talking. With her wild imagination, great storytelling, and deep understanding of folly and the human heart, the beloved Fannie Flagg tells an unforgettable story of life, afterlife, and the remarkable goings-on of ordinary people. In The Whole Town’s Talking, she reminds us that community is vital, life is a gift, and love never dies. Praise for The Whole Town’s Talking “A witty multigenerational saga . . . [Fannie] Flagg’s down-home wisdom, her affable humor and her long view of life offer a pleasant respite in nerve-jangling times.” — People   “Fannie Flagg at her best.” — The Florida Times-Union   “If there’s one thing Fannie Flagg can do better than anybody else, it’s tell a story, and she outdoes herself in The Whole Town’s Talking . . . . Brilliant . . . equally on the level as her famous Fried Green Tomatoes at the Whistle Stop Cafe .” — The Newport Plain Talk   “Delightful.” —The Washington Post   “A ringing affirmation of love, community and life itself.” — Richmond Times-Dispatch